Nature-based solutions for climate adaptation: Review of barriers to adoption and guidelines for policymakers - Anita Vollmer; Stefano Ceolotto; Niall Farrell (The Economic and Social Research Institute (ESRI), 2024)
Nature-based solutions (NBS) for climate adaptation encompass a range of approaches that work with nature to increase resilience to climate change whilst providing ecological and social co-benefits. These solutions have frequently been put forward for application in urban contexts, such as the creation of urban forests, but can likewise be applied to rural contexts where they may, for example, prevent soil erosion. However, NBS face numerous barriers to being considered on equal footing with technical climate adaptation interventions. Previous research that has sought to address this issue has focused on conceptual frameworks, on the one hand, and practical guidance on how to quantify the benefits provided by NBS, on the other. In this article, we supplement these existing frameworks by providing practical recommendations for the whole decision-making cycle, from identification of objectives to the monitoring and scaling up of chosen interventions. We draw from a wide range of literature to, first, outline the barriers to the inclusion of NBS and, second, present policy recommendations for each step of the climate adaptation process. We find that policy recommendations which span across all decision-making steps are: Choosing a participatory decisionmaking approach, involving a wide range of experts, considering social justice implications, and creating a legal and regulatory framework which can accommodate NBS. While we put an emphasis on climate adaptation, most of the recommendations presented here are not limited to this context.
Keywords: 330; Climate adaptation; Nature-based solutions; Ecosystem services; Policy decision-making; Planning